HUBUNGAN PERILAKU PENCARIAN INFORMASI DENGAN PROSES PENGAMBILAN KEPUTUSAN SWING VOTERS PADA PILPRES 2024 - Nadia Nur Azizah; Sukaesih, Sukaesih; Saepudin, Encang (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2024)
(Objectives) Swing voters are rational individuals who may be indecisive in making choices. Consequently, they seek information that addresses their personal goals or preferences when selecting among available alternatives. Specifically, swing voters among students tend to be objective and rational in their decision-making. This study aims to understand the relationship between information-seeking behavior and the decision-making process of swing voters in the 2024 Presidential Election. (Method) Data collection was conducted using a questionnaire that measured information-seeking behavior variables based on the Ellis model, encompassing the stages of starting, chaining, browsing, differentiating, monitoring, extracting, verifying, and ending. The population consisted of first-time voters from the 2023 Fikom Unpad class, with a sample of 89 students determined using non-probability sampling techniques and the Slovin formula. This study employs a quantitative approach with Spearman rank correlation analysis techniques.  (Findings) The results indicate that information-seeking behaviour is related to the decision-making process in a high category, with a positive direction of the relationship. In other words, the better the information-seeking behaviour of voters, the better the decision-making process is reflected. This suggests that how swing voters acquire and use information as part of their information-seeking behaviour plays a crucial role in determining the quality of their choices. This research is expected to serve as a reference for similar studies in the future and specifically to help swing voters find choices that align with their personal preferences.